Developing Learning Media for Deaf Students of SMPLB Muhammadiyah Jombang; SIAGA (Speaking Skills Games) - Agustina, Ulfa Wulan; Pujiani, Tripujiani; Afidah, Nurul; Mufida, Cici Nur (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2024)
This study focuses on developing a learning medium using PowerPoint called SIAGA (Speaking Skills Games) to enhance the speaking skills in English of grade-eight deaf students at SMPLB Muhammadiyah Jombang. Considering that speaking is an important skill in communication, the research addresses the unique challenges faced by deaf students, such as delayed language development and reliance on visual learning. Utilizing R&D Method with ADDIE design, some concepts of gamification were combined with visual aids, animations, and sign language in this learning module to better respond to the needs of Deaf students. The application SIAGA was developed through consultation with experts, and then it went through validation procedures by media, language, and disability specialists. From these, the feedback about the relevance was 95% and that on media design was 79%, suggesting the need to improve the visuals, font readability, and clarity in instructions. In sum, post-implementation evaluations through student questionnaires averaged 89% regarding the effectiveness, ease of use, and motivational effect of the application. Application research in inclusive classrooms involving both deaf and hearing students would be valuable for further study of this medium.